Estado nutricional y su relación con los hábitos alimentarios en los niños y niñas de 1 a 3 años de edad del Centro de Desarrollo Infantil Nuevo Amanecer del barrio San Carlos, Parroquia Zumbi, cantón Centinela del Cóndor, periodo septiembre 2018 - Carrión Peralta, Joselyn Katherine (2019)
The objective of this thesis is to evaluate the nutritional status and its relationship to eating habits. This investigation adopted a quantitative approach of a descriptive, correlational and transversal nature. It was carried out at the “Nuevo Amanecer” Child Development Center located in the San Carlos Neighborhood, Zumbi Parish, in the Canton Centinela del Condor in the Province of Zamora Chinchipe pertaining to Zone 7. The sample consisted of 33 children and their legal representatives, on whom an assessment of nutritional status was administered with respect to anthropometric measures of weight, height and body mass index and a survey was conducted with the parents in order to learn about their eating habits. The result was that 91% of boys and girls were of normal weight, 6% were suffering from malnutrition and 3% were overweight. According to the types of food and the frequency of their consumption, it was found that 45.4% consumed food four to five times a day, 51.5% drank 1 to 2 glasses of water a day, 63.6 % ate fruit, 51.5% consumed meat, fish and shellfish it once a week, 63.6% preferred cereals, milk was consumed by 66.7%, and 69, 7% ingested vegetables. By relating the two variables, the 81.8% that demonstrated good eating habits belonged to the normal weight group; 18.2% with inadequate eating habits possessed an inappropriate nutritional status and were at risk. It is concluded that there is a significant relationship between nutritional status and eating habits. Keywords: Body mass index, nutritional practices, nutrition.